2016
DOI: 10.1210/jc.2015-4191
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly Is More Severe in Patients With AHR or AIP Gene Variants Living in Highly Polluted Areas

Abstract: Genetic variants potentially inducing functional abnormalities of the aryl hydrocarbon receptor (AHR) pathway are associated with a more severe acromegaly, increased pituitary tumor size, and somatostatin analog resistance in patients living in HR areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…From a clinical viewpoint, patients carrying AIP mutations are more often young, male and with large GH- or mixed GH- and prolactin-secreting tumors [48, 53, 54]. Interestingly, the AhR gene itself appears to contribute to severity of acromegaly as polymorphisms and variants in AhR have been associated with more aggressive disease [55, 56]. …”
Section: Discussionmentioning
confidence: 99%
“…From a clinical viewpoint, patients carrying AIP mutations are more often young, male and with large GH- or mixed GH- and prolactin-secreting tumors [48, 53, 54]. Interestingly, the AhR gene itself appears to contribute to severity of acromegaly as polymorphisms and variants in AhR have been associated with more aggressive disease [55, 56]. …”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly was observed with increased incidence in a highly polluted industrial region in Italy (Messina, Sicily) (79). The current prevalence of acromegaly is thought to be 330 cases per million inhabitants and the relative risk of developing the disease was estimated to be eight-fold higher in comparison with a non-polluted area in the same province (79,80). In a subsequent study it was found that 9/23 (39%) patients from different highly polluted areas in Italy bore a genetic variant of AHR or AIP, as compared with 25.3% (44/187) of patients from non-polluted regions.…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…In a subsequent study it was found that 9/23 (39%) patients from different highly polluted areas in Italy bore a genetic variant of AHR or AIP, as compared with 25.3% (44/187) of patients from non-polluted regions. Notably, genetically variant adenomas in polluted areas had a more severe course of acromegaly, characterized by higher IGF-1 values and larger tumor size and worse response to first-line SSAs in comparison with the other groups (80). It is known that AIP forms a complex with AHR, stabilizing it in the cytoplasm together with a dimer of heat-shock proteins 90 and the co-chaperone p23 and AIP protein expression could influence AHR expression (78,81,82).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…Taking together these results indicate that BZ is an environmental factor that could play an important role in pituitary adenoma responsiveness to SSA therapy. At present, only indirect evidence of the role of benzene exposure in SSA resistance in humans with GH-producing adenomas are available (Cannavò et al 2016). Indeed, in 2016 Cannavò et al observed more frequent SSA resistance in acromegalic patients living in highly polluted areas and carriers of AHR genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…In the highly polluted area close to Messina (Italy) Cannavò et al (2010) encountered a significantly higher prevalence of acromegaly respect to less polluted areas and to the general population. Patients living in highly polluted areas and carriers of genetic variants affecting normal functioning of the aryl hydrocarbon receptor (AHR) pathway (that is involved in xenobiotics cellular response) present larger pituitary tumors, more severe acromegaly symptoms, and are more frequently SSA resistance (Cannavò et al 2016).…”
Section: Introductionmentioning
confidence: 99%